2017
DOI: 10.1080/17482631.2017.1392219
|View full text |Cite|
|
Sign up to set email alerts
|

“It´s incredible how much I´ve had to fight.” Negotiating medical uncertainty in clinical encounters

Abstract: Purpose: Clinical encounters related to medically unexplained physical symptoms (MUPS) are associated with high levels of conflict between patients and doctors. Collaborative difficulties are fused by the medical uncertainty that dominates these consultations. The main aim of this study is to explore the interactional dynamics of clinical encounters riddled by medical uncertainty, as experienced by people living with long-term medically unexplained fatigue in Norway. Method: A qualitative thematic analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 50 publications
(60 reference statements)
3
30
0
1
Order By: Relevance
“…We found that family, friends, health care providers, and even strangers had difficulty understanding the profound impact of fatigue on psychosocial wellbeing. The responses of family and friends may be influenced by that of clinicians, and as Lian and Robson 48 noted health care professionals often respond to medically unexplained symptoms such as fatigue with disbelief, inappropriate psychological explanations, marginalization of experiences, disrespectful treatment, lack of physical examination, and damaging health advice. Others have noted that patients are often not even asked about fatigue by their health care professionals.…”
Section: Discussionmentioning
confidence: 99%
“…We found that family, friends, health care providers, and even strangers had difficulty understanding the profound impact of fatigue on psychosocial wellbeing. The responses of family and friends may be influenced by that of clinicians, and as Lian and Robson 48 noted health care professionals often respond to medically unexplained symptoms such as fatigue with disbelief, inappropriate psychological explanations, marginalization of experiences, disrespectful treatment, lack of physical examination, and damaging health advice. Others have noted that patients are often not even asked about fatigue by their health care professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Research pertaining to uncertainties within medicine in general more broadly demonstrate the need to operationalize conceptual frameworks of uncertainty to address its consequences (Bhise et al, ), a conclusion that translates well into genomic medicine. Previous assessments on uncertainty management strategies emphasize the basic need for providers to openly communicate about uncertainty, acknowledge patients' unique perspectives and concerns, and practice shared decision making (Alam et al, ; Kennedy, ; Lian & Robson, ; Schneider, Wübken, Linde, & Bühner, ). These recommendations reflect practice‐based competencies the Accreditation Council for Genetic Counseling have highlighted as essential skills for the successful practice of genetic counselors.…”
Section: Discussionmentioning
confidence: 99%
“…ME/CFS is potentially life-shortening, although registered deaths from ME/CFS are rare; between 2001 and 2016, 88 deaths in England and Wales were partly or fully attributable to ME/CFS [12]. This is a disease of low prestige, and PWME often experience damaging negative encounters with GPs, nurses, and other healthcare practitioners (HCPs) [13]; disrespectful treatment and trivialising of legitimate symptoms may lead to loss of agency and alienation from all medical services. PWME are often made to feel, in the words of one parent carer, "that they are second-class citizens, malingerers or at least somehow responsible for their own misfortune" [14].…”
Section: Me/cfs and The Needs Of The Severely Affected Individualmentioning
confidence: 99%